Engineering properties of compressed bricks based on stabilised peat soils / Sadek Deboucha. - Sadek, Deboucha (2011)
Earth as a building material is available everywhere and exists in many different compositions. It is most efficiently used in developing countries to cater for the greatest number of people. With the increased awareness of climate change issues, it is now generally accepted that there is an urgent need to limit carbon dioxide emissions into the atmosphere. These emissions are becoming a major environmental concern in tropical countries. The research looked into the use of peat soil, a waste material in many construction works. There is no requirement for burning, hence saving energy and minimise emissions. The thesis examines the interplay between three main factors: constituent materials (cement, soil, sand and suitable pozzolan materials), compaction pressure and the processing methods for bricks fabrication. Laboratory investigation was carried out to investigate the relation between mix design and the engineering performance taking into consideration the economic factors. The research examined the effects of chemical binders and sand at improving peat soil as solid and hollow bricks in terms of engineering properties including wet and dry compressive strength, total water absorption, bulk and dry density and total volume porosity. The characteristics of airborne sound insulation, fire resistance and axial load capacity of compressed stabilised peat masonry wall were also investigated. Laboratory finding showed that peat based compressed bricks have the required physical properties to be used as construction bricks. Compressive strength of compressed stabilised peat bricks prospectively for PFA cement, PFA cement with lime, and OPC with lime, were 7.2 MPa, 7.66 MPa and 6.77 MPa which the minimum recommended strength for brick and block is 2 MPa. The highest compressive strength results were derived from the mixture of compressed stabilised peat brick was when used PFA cement and high compaction pressure. For water absorption test of compressed stabilised peat bricks gained the best results of only 2.6%, which water absorption recommended by BS 3921 is 4.5% for category A and 7% for category B. The volume porosity test of compressed stabilised peat bricks obtained good results of only 4.75%, which maximum values recommended by BS 3921 is 10%. Sound transmission and fire resistance in housing is a problem that exists in many countries. Compressed stabilised peat bricks sound insulation and fire resistance results indicated that an effective condition for construction insulation and fire resistance. Validation of the experimental results of the compressed stabilised peat brick masonry prism tests affirmed that the stress-strain of masonry prism evaluated experimentally could be reasonably back analyzed by the finite element method. The finite element program was then used to establish the various configuration of compressed stabilised peat masonry wall. The thesis concludes that it is possible to significantly raise the strength and improve the engineering properties of compressed stabilised peat brick. This improvement is achieved via better bonding, reduction in voids and lowered water absorption. Hence, peat soils can be engineered to produce bricks and blocks for the construction industry.